Exploring Perception of EFL Teachers towards Use of Media in Teaching English - Nany Soengkono Madayani; Muhassin Muhassin (IJOTL-TL: Indonesian Journal of Language Teaching and Linguistics, 2020)
This Research is against the backdrop of demand in mastering English. EFL teacher becomes one of the main important parts of teaching-learning English to handle a certain role in maximal the students’ achievement. The students’ achievement here means not only someone that has a lot of knowledge and high value but also someone that can give a positive contribution to other people. Because of that, the teachers have a big responsibility to facilitate students in learning. One of the facilitation of teaching-learning that has to be prepared by teachers is media. This study aims to investigate the teachers’ perceptions of ELT media. This study is classified into three main dimensions of perception proposed by Vernon (1987) namely understanding, outlook and action. By conducting a survey study, the researcher collected, analyzed, elaborated and eventually drew conclusions dealing with the teachers’ perceptions of ELT media. The main data of this study were collected with an interview and a questionnaire, which was distributed to 29 English teachers in the city of Tulungagung. The findings showed that Media is able to be a benefit for both teachers and students, be applicable to every class. To select criteria of Media is based on Media Mastery or flexibility due to different reference and less facility. Besides that, The teachers have positive responses towards the two of the dimensions, understanding, and view. The teachers, however, do not show positive responses toward the action. However, in general, the English teachers’ perceptions of ELT media in this study were categorized as a good perception. In other words, all the teachers have a positive perception of ELT media.